Penerapan Computational Thinking dalam Pembelajaran IPA Materi Susunan Tulang Daun pada Kelas IV di SD Kanisius Klepu - Siti Wahyuni; Dwi Kurniati Rofingah; Christiyanti Aprinastuti; Utami Jati (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The purpose of this study was to describe the application of Computational Thinking in learning science on the material of leaves for class IV at Kanisius Klepu Elementary School. This type of research is descriptive research, descriptive research is a form of research, aimed at describing phenomena that exit in natural phenomena and artificial phenomena. Respondents in this study were fourth grade students at SD Kanisius Klepu with a total of 25 student. This research was conducted on March 9 2023 in class IV SD Kanisius Klepu. Data collection techniques in this study used tests and questionnaires. The results of this study indicate that there are still students who do not have the knowledge and skills of Computational Thinking that are implemented in science learning. The learning process integrates the concept of Computational Thinking aspectcts of pattern recognition, abstraction and algorithms. Based on the student worksheet the results, the learning completeness was 75% in the good category.